Clinical impact of direct stenting and interaction with thrombus aspiration in patients with ST-segment elevation myocardial infarction undergoing percutaneous coronary intervention: Thrombectomy Trialists Collaboration. (21st April 2018) - Mahmoud, Karim D; Jolly, Sanjit S; James, Stefan; Džavík, Vladimír; Cairns, John A; Olivecrona, Goran K; Renlund, Henrik; Gao, Peggy; Lagerqvist, Bo; Alazzoni, Ashraf; Kedev, Sasko; Stankovic, Goran; et al.
Abstract: Aims: Preliminary studies suggest that direct stenting (DS) during percutaneous coronary intervention (PCI) may reduce microvascular obstruction and improve clinical outcome. Thrombus aspiration may facilitate DS. We assessed the impact of DS on clinical outcome and myocardial reperfusion and its interaction with thrombus aspiration among ST-segment elevation myocardial infarction (STEMI) patients undergoing PCI. Methods and results: Patient-level data from the three largest randomized trials on routine manual thrombus aspiration vs. PCI only were merged. A 1:1 propensity matched population was created to compare DS and conventional stenting. Synergy between DS and thrombus aspiration was assessed with interaction P -values in the final models. In the unmatched population ( n  = 17 329), 32% underwent DS and 68% underwent conventional stenting. Direct stenting rates were higher in patients randomized to thrombus aspiration as compared with PCI only (41% vs. 22%; P  < 0.001). Patients undergoing DS required less contrast (162 mL vs. 172 mL; P  < 0.001) and had shorter fluoroscopy time (11.1 min vs. 13.3 min; P  < 0.001). After propensity matching ( n  = 10 944), no significant differences were seen between DS and conventional stenting with respect to 30-day cardiovascular death [1.7% vs. 1.9%; hazard ratio 0.88, 95% confidence interval (CI) 0.55–1.41; P  = 0.60; P interaction = 0.96) and 30-day stroke or transient ischaemic attack (0.6% vs. 0.4%; odds ratio 1.02; 95% CI 0.14–7.54; P  = 0.99; P interaction = 0.81). One-year results were similar. No significant differences were seen in electrocardiographic and angiographic myocardial reperfusion measures. Conclusion: Direct stenting rates were higher in patients randomized to thrombus aspiration. Clinical outcomes and myocardial reperfusion measures did not differ significantly between DS and conventional stenting and there was no interaction with thrombus aspiration.